Carbon Capture and Energy Storage, Protect the Earth - Jin, Jia-Min; fang, Bao wei (European Journal of Applied Sciences, 2022)
There are two contents of this article. The first is briefly to review the experiment research on the catalysis mechanism of Carbon Gasification Reaction-CGR(C+CO2=2CO) from 60s -90s . The results show that the catalytic phenomenon is physical phenomenon rather than chemical, and the catalyst does not participate in the chemical reaction. The catalytic activity and selectivity of catalyst are related to the electronegativity or energy level of the catalyst. The second is to clarify the applications of CGR for save mankind . The lime is first proposed to capture CO2 in flue gas of power plant. The lime can be recycled. The coal is used to convert CO2 from cement steel produce into CO, producing both energy and lime and iron. The capture CO2 is used to treat waste such as firewood and plastic, eliminate white pollution . The author considers that using the CGR which has been used for a long time can solve the three problems which people worry about: energy exhaustion, environmental pollution and climate crisis.